2014
DOI: 10.1007/jhep09(2014)093
|View full text |Cite
|
Sign up to set email alerts
|

Topological invariants and fibration structure of complete intersection Calabi-Yau four-folds

Abstract: Abstract:We investigate the mathematical properties of the class of Calabi-Yau fourfolds recently found in ref. [1]. This class consists of 921,497 configuration matrices which correspond to manifolds that are described as complete intersections in products of projective spaces. For each manifold in the list, we compute the full Hodge diamond as well as additional topological invariants such as Chern classes and intersection numbers. Using this data, we conclude that there are at least 36,779 topologically dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(107 citation statements)
references
References 25 publications
1
105
0
1
Order By: Relevance
“…The asymptotic behaviour of the central charge of a B-brane F • in the limit of large volume can be calculated using the Γ-class formula [47] 4) where in terms of the Chern classes c 2 , c 3 of M Γ C (M ) = 1 + 1 24…”
Section: Modularity From Monodromymentioning
confidence: 99%
“…The asymptotic behaviour of the central charge of a B-brane F • in the limit of large volume can be calculated using the Γ-class formula [47] 4) where in terms of the Chern classes c 2 , c 3 of M Γ C (M ) = 1 + 1 24…”
Section: Modularity From Monodromymentioning
confidence: 99%
“…We will consider a particular existent Line Bundle Standard Model data set [19,20] built over Calabi-Yau manifolds which can be described as quotients of complete intersections in products of projective spaces (CICYs) [70][71][72][73][74][75][76]. Note that analogous constructions could be pursued over different base spaces, such as quotients of gCICYs [77] or toric hypersurfaces [78][79][80][81][82].…”
Section: Heterotic Line Bundle Standard Modelsmentioning
confidence: 99%
“…The largest known set of Calabi-Yau threefolds are constructed from the class of over 400 million reflexive 4D polytopes found by Kreuzer and Skarke [5,6], and exhibit this mirror symmetry structure. More recently, an increasing body of evidence [7][8][9][10][11][12][13][14][15][16] suggests that a large fraction of known Calabi-Yau threefolds have the property that they can be described as genus one or elliptic fibrations over a complex two-dimensional base surface. We recently showed that this is true of all but at most 4 Calabi-Yau threefolds in the Kreuzer-Skarke database having one or the other Hodge number h 2,1 , h 1,1 at least 140, and that at small h 1,1 the fraction of polytopes in the Kreuzer-Skarke database that lack an obvious elliptic or genus one fibration decreases roughly as 0.1 × 2 5−h 1,1 .…”
Section: Contentsmentioning
confidence: 99%